Journal Economics, business & accountancy : THE EFFECT OF MARKET ORIENTATION ON PERFORMANCE WITH ENVIRONMENTAL UNCERTAINTY AS A MODERATING VARIABLE - Hudayah, Syarifah, Ikbal, Muhammad (PPPM Perbanas, 2013)
Market orientation of banks is related to business performance through the environmentaluncertainty as moderator. Environmental uncertainty is an important factor in both the marketingand management literature. In this case, it is important to see how an increase in environmentaluncertainty influences the market orientation – performance relationship. Data forthis study were collected using questionnaires mailed to the top executives throughout 132local development banks (BPD) in 30 state-regions (province) in Indonesia, representing allthe local development banks